THE KNOWLEDGE ABOUT BABY MUMS FAREL MASSAGE IN BPM BEKTI SAYEKTI TARUBASAN KARANGANOM KLATEN - STIKES DUTAGAMA KLATEN (STIKES DUTAGAMA KLATEN, 2014)
Background: One way to improve volume breast-fed cheap and easy it is massage baby. He pemijatan in infants purpose is to provide a comfortable in a baby. To accomplish a purpose pemijatan farel mother acquired a knowledge about massage baby. Preliminary study in bekti sayekti, bpm mother, an interview from 10 there are seven mother less know about massage farel good understanding purpose, benefits. Objective: To know the level of knowledge about babies in mums farel massage BPM Bekti Sayekti Tarubasan Karanganom Klaten. Method: A method of research is descriptive. Samples research 32 respondents taken in total of sampling. Instrument used a questionnaire. Data analysis using analysis univariat. Result: Characteristic of a mother by age is farel 20-35 years amounting to 90,6 %, based on education is smas / smk rp59.22 65,6 % and work is based on works by 62.5 %. The knowledge about mums farel massage farel namely. 50 % knowledgeable good. 40,6 % enough and 9.4 % less. Conclusion: The knowledge about babies in mums farel massage bpm bekti sayekti tarubasan karanganom klaten is good. Mother is expected to retain knowledge and more routine memijatkan the baby especially in the age beginning of his birth.